Cognition, Corpora, and Computing: Triangulating Research in Usage‐Based Language Learning. (14th December 2016) - Ellis, Nick C.
Abstract : Usage‐based approaches explore how we learn language from our experience of language. Related research thus involves the analysis of the usage from which learners learn and of learner usage as it develops. This program involves considerable data recording, transcription, and analysis, using a variety of corpus and computational techniques, many of them specially devised for learner language. This article surveys relevant developments across the psychology of learning, first and second language acquisition, psycholinguistics, corpus linguistics, and computational linguistics and identifies challenges and future priorities relating to the following issues: (1) analyzing the distributional characteristics of linguistic constructions and their meanings in large collections of language that are representative of the language that learners experience, (2) the longitudinal analysis of learner language, and (3) Natural Language Processing analyses of the dimensions of language complexity.